Effect of environmental factors on the synthesis and properties of Acinetobacter sp. exopolysaccharides - Pirog, Tatiana; Grinberg, Tamara; Malashenko, Yuri (My University, 1998)
Effects of external factors on the synthesis and physicochemical properties of Acinetobacter sp. exopolysaccharides (EPSs), which determine the biological functions of this microorganism, were studied. The cultivation temperature, medium pH, and oxygen concentration in the medium (p02) affected the viscosity of EPS solutions in the presence of monovalent cations, in the H+-form, and in a Cu2+-glycine system. All the EPSs studied were precipitated with heavy metal ions (Cr3+, Cu2+, Pb2+, Cd2+, etc.). No changes in the EPS yield were observed under unfavorable environmental conditions. At high pO2 values (up to 80% of saturation), the maximum specific rates of bacterial growth and EPS synthesis increased. It was suggested that Acinetobacter sp. EPSs perform different biological functions under optimal and nonoptimal conditions.
Keywords: exopolysaccharides; unfavorable factors; biological functions; экзополисахариды; неблагоприятные факторы; биологические функции; екзополісахариди; несприятливі фактори; біологічні функції; кафедра біотехнології і мікробіології